2023
DOI: 10.1007/s00204-023-03491-7
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exposure to multiple mycotoxins and adverse pregnancy outcomes: a prospective cohort study in rural Bangladesh

Abstract: There is limited and inconsistent evidence, primarily from cross-sectional studies, linking mycotoxins to adverse birth outcomes. This study investigates the potential role of maternal dietary exposure to multiple mycotoxins in the development of several adverse pregnancy and birth outcomes. We analyzed data from 436 singleton pregnancies enrolled in a prospective cohort study in the rural Habiganj district, Bangladesh, between July 2018 and November 2019. Thirty-five urinary mycotoxin biomarkers were quantifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…Pregnant women may be exposed to multiple mycotoxins simultaneously by dietary, since similar environmental conditions could produce several mycotoxins in foods at the same time [ 46 ]. Although a cohort study in Bangladesh reported that maternal dietary intake of ochratoxin A was associated with higher risk of having an LBW baby, it did not find a difference between exposure alone and combined exposure to other mycotoxins [ 47 ]. Therefore, further epidemiological studies are needed to evaluate the complex effects of co-exposure of mycotoxins on the health risk in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women may be exposed to multiple mycotoxins simultaneously by dietary, since similar environmental conditions could produce several mycotoxins in foods at the same time [ 46 ]. Although a cohort study in Bangladesh reported that maternal dietary intake of ochratoxin A was associated with higher risk of having an LBW baby, it did not find a difference between exposure alone and combined exposure to other mycotoxins [ 47 ]. Therefore, further epidemiological studies are needed to evaluate the complex effects of co-exposure of mycotoxins on the health risk in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, the co-occurrence of multiple mycotoxins in cereals presents a complex challenge due to potential interactions among these compounds. 3,9 Thus, developing a reliable and robust method for accurately quantifying multiple mycotoxins in cereals holds paramount significance. 2,4 Over the past two decades, liquid chromatography coupled with triple quadrupole mass spectrometry (LC-MS/MS) and high-resolution mass spectrometry have attracted widespread popularity for mycotoxin determination due to their inherent specificity, sensitivity, and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The trichothecenes encompass a substantial array of mycotoxins, where deoxynivalenol (DON) and zearalenone (ZEN) are the most commonly contaminated in harvested products such as maize and wheat. ,, In light of the widespread contamination and toxicity of mycotoxins in cereals, feeds, and other consumables, stringent limits for the major mycotoxins in grains have been established by many countries . However, the co-occurrence of multiple mycotoxins in cereals presents a complex challenge due to potential interactions among these compounds. , Thus, developing a reliable and robust method for accurately quantifying multiple mycotoxins in cereals holds paramount significance. , …”
Section: Introductionmentioning
confidence: 99%
“…Humans are unknowingly exposed to FBs through food intake due to mycotoxins are difficult to monitor continuously, and a tools to assess the risk are poor [42][43][44]. Prenatal FBs exposure results not only in altered prenatal development, disturbances in the structure and function of bone and the gastrointestinal tract (liver, intestine, including enteric nervous system), impaired hematopoiesis and inflammation in skeletal muscles, it also leads to endocrine alterations resulting in disproportional development and increased risk of diabetes mellitus [12,37,[45][46][47][48][49][50][51]. Considering FBs-exposure results in various health problems, including imbalances in the collagenous and non-collagenous bone proteins involved in bone turnover, it seems reasonable to further investigate the effects of prenatal FBs exposure on bone metabolism, which is important in the development of the whole organism and its functioning.…”
Section: Introductionmentioning
confidence: 99%